Prevalence of musculoskeletal pain associated with working time and magnification in endodontists from Ecuador - Vinueza Idrovo , Nicole Estefania (2026)
Objectives: To assess the prevalence and location of musculoskeletal pain, as well as its potential association with working hours and the use of magnification, among endodontists in Ecuador. Materials and Methods: An observational, cross-sectional study was conducted among 255 practicing endodontists. A modified Nordic Questionnaire was administered electronically, collecting data on demographics, magnification use, workload, and the presence of pain in the last 12 months and 7 days. Data were analyzed in SPSS using ANOVA and chi-square tests, with statistical significance set at p < 0.05. Results: 76.9% of participants reported musculoskeletal pain in the past year. The most affected regions were the lower back (59.7%), neck (54.1%), and upper back (54.1%). 39.2% reported pain within the last 7 days, 18.8% temporarily suspended clinical practice, and 29.8% required medical or physiotherapeutic care. Prevalence was higher among professionals with fewer than 5 years of experience (89.9%) and those working more than 41 hours per week (78%), both associations being statistically significant (p < 0.001). The use of magnification was associated with a lower prevalence of pain (72.0% vs. 80.4%), though this difference was not statistically significant (p = 0.0789). Conclusions: Musculoskeletal pain is highly prevalent among Ecuadorian endodontists, particularly in the lumbar and cervical regions, and is associated with higher workload and less clinical experience. Although magnification use showed a protective trend, it was not statistically significant. These findings underscore the need for ergonomic programs and preventive strategies in clinical practice.